A long-awaited taxogenomic investigation of the family Halomonadaceae - de la Haba, Rafael R.; Arahal, David R.; Sánchez-Porro, Cristina; Chuvochina, Maria; Wittouck, Stijn; Hugenholtz, Philip; Ventosa, Antonio (Frontiers in Microbiology, 2023)
The family Halomonadaceae is the largest family composed of halophilic bacteria, with more than 160 validly published species names as of March 2023. Several classifications to circumscribe this family are available in mayor resources, such as those provided by the List of Prokaryotic names with Standing in Nomenclature (LPSN), NCBI Taxonomy, Genome Taxonomy Database (GTDB), and Bergey's Manual of Systematics of Archaea and Bacteria (BMSAB), with some degree of disagreement between them. Moreover, regardless of the classification adopted, the genus Halomonas is not phylogenetically consistent, likely because it has been used as a catch-all for newly described species within the family Halomonadaceae that could not be clearly accommodated in other Halomonadaceae genera. In the past decade, some taxonomic rearrangements have been conducted on the Halomonadaceae based on ribosomal and alternative single-copy housekeeping gene sequence analysis. High-throughput technologies have enabled access to the genome sequences of many type strains belonging to the family Halomonadaceae; however, genome-based studies specifically addressing its taxonomic status have not been performed to date. Here, we accomplished the genome sequencing of 17 missing type strains of Halomonadaceae species that, together with other publicly available genome sequences, allowed us to re-evaluate the genetic relationship, phylogeny, and taxonomy of the species and genera within this family. The approach followed included the estimate of Overall Genome Relatedness Index (OGRI) such as the Average Amino acid Identity (AAI), phylogenomic reconstructions using amino acid substitution matrices customized for the family Halomonadaceae, and the analysis of clade-specific signature genes. Based on our results, we conclude that the genus Halovibrio is obviously out of place within the family Halomonadaceae and, on the other hand, we propose a division of the genus Halomonas into seven separate genera, and the transfer of seven species from Halomonas to the genus Modicisalibacter, together with the emendation of the latter. Additionally, data from this study demonstrate the existence of various synonym species names in this family.